Peer Education Prevents Sexual Risk Behavior Among Adolescents in Rural Area - Sri Andini Widya Ningrum; Sri Sumaryani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2017)
Introduction :Adolescence as a transitional period can be a problem because there are many changes in it, both physically, psychologically, and intellectually, that make them as a population vulnerable to perform risky behaviors, included sexual risk behavior. Peers have an important role in the social life of adolescents because teenagers spend more time with friends and generally teens also make their peers as a role model in behaving.This study aims to determine the effect of peer-based education in the prevention of sexual risk behavior among adolescents in rural areas Methods:This type of research is a pre-experimental quantitative study with a one-group pre-post test design. The research was conducted on April-June 2017 with 61 respondents which were selected by purposive sampling method. The research instrument used questionnaire. Results :The result of data analysis used Paired Simple T Test was found that there were significant differences in the prevention of sexual risk behavior among adolescents in rural area before and after been given sexual education through peer education with p value (0,002).Proper timing of education, a conducive environment and a good concentration in learning make education work optimally.Conclusions :There is a significant effect of peer education in the prevention of sexual risk behavior among adolescents in rural areas. It is recommended to conduct research in other regions with different characteristics